Cover Picture: A Desymmetrization‐Based Total Synthesis of Reserpine (Angew. Chem. Int. Ed. 49/2018). Issue 49 (31st October 2018) - Park, Jisook; Chen, David Y.‐K.
Abstract : A desymmetrization‐based approach to the fused polycyclic indole alkaloid reserpine has been accomplished by D. Y.‐K. Chen and J. Park in their Communication onpage 16152. The centerpiece of the developed strategy featured an internal desymmetrization process that enabled the use of a readily accessible and non‐stereogenic reserpine E‐ring precursor; in stark contrast to the stereo‐defined E‐ring intermediates employed in all past reserpine syntheses.